Escherichia coli O157:H7 Contamination Level in Dairy Farms in Yogyakarta Special Region - Primasito, Anggit; Nugroho, Widagdo Sri; Widartono, Barandi Sapta (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2026)
Escherichia coli O157:H7 is a zoonotic pathogenic microorganism that can cause serious infections in humans. Transmission from animals to humans due to contamination of animal products, especially milk, has been reported. The aim of this study was to calculate the level of Escherichia coli O157:H7 contamination and analyze the risk factors on dairy farms in Yogyakarta Special Region. The study involved 106 farms with milk samples from 460 dairy cows, 106 soil samples, 106 stable floor swab samples and 106 milker’s hand swab samples. Isolation and identification using MacConkey media and Indole, Methyl Red, Voges-Proskauer, Citrate (IMVic) media. Identification of Escherichia coli O157:H7 with Sorbitol MacConkey media and Polymerase Chain Reaction (PCR) with Stx1, Stx2 gene targets. Risk factor data were collected through observation and interviews with farmers and analyzed by descriptive statistics and multivariable logistic regression using SPSS. The results showed 72 out of 106 farms were positive for Escherichia coli (67.92%) with 94 milk samples, 17 soil, 11 cage floor swabs, 15 milkers' hand swabs. Five out of ninety-four milk-derived Escherichia coli isolates were identified as Escherichia coli 0157:H7 and spread across five farms (4.7%). Logistic regression results showed that the risk factors for Escherichia coli contamination in dairy farms in Yogyakarta Special Region are presence of other livestock species, cage conditions, cage disinfection, waste management and presence of streams.